PREDIKSI TINGKAT PENCEMARAN AIR SUNGAI MENGGUNAKAN INDEKS KIMIA-FISIKA DAN METRIK BENTIK MAKROINVERTEBRATA - Syamsul Bahri (JURNAL SUMBER DAYA AIR, 2007)
Application of numeric benthic macroinvertebrate indices to predict river water pollution categories waspoorly developed in Indonesia. A lack of information in this numeric indices study caused Indonesia be leftbehind in developing this science, consequently this method was not yet applied in routinely based rivermanagement. The main objectives of this research are: a). to examine the suitability of three benthicmacroinvertebrate metrics to water chemical-physical index b). to assess test site based on water pollutioncategories. Survey method was used as research methodology. Water sampling and its analysis were done infield and laboratory. Standar Nasional Indonesia (SNI) was used as water quality analysis method. Scoringof LAWA was used to evaluate the chemical-physical index, whereas categorization and classification ofwater quality was based on the saprobic classification. As related to the correlation test, highest coefficientvalue was shown by score Biological Monitoring Working Party (BMWP) (r = 0,89) compared to a metrictaxa richness (r = 0,84), and diversity index (r = 0,57). Therefore, BMWP score is indicating thatclassification of water pollution in Ciliwung River can be divided into three categories: moderately polluted,critically polluted and heavily polluted.